Gender Conflicts : New Essays in Women's History - Valverde, Mariana, 1955-; Iacovetta, Franca, 1957- (Book collections on Project MUSE., 1992)
In the early 1970s, when women's history began to claim attention as an emerging discipline in North American universities, it was dominated by a middle-class Anglo-Saxon bias. Today the field is much more diverse, a development reflected in the scope of this volume. Rather than documenting the experiences of women solely in a framework of gender analysis, its authors recognize the interaction of race, class, and gender as central in shaping women's lives, and men's.These essays represent an exciting breakthrough in women's studies, expanding the borders of the discipline while breaking down barriers between mainstream and women's history.